Pemberdayaan Perempuan dalam Upaya Meningkatkan Kualitas Kesehatan Masyarakat melalui Pemahaman Bentuk Sediaan, Kemasan, Keamanan dan Stabilitas Obat di Kabupaten Magetan untuk Mendukung SDG’s 3 - Sari, Retno; M. Agus Syamsur Rijal; Andang Miatmoko; Dini Retnowati; Dewi Isadiartuti; , Idha Kusumawati; Noorma Rosita; Tutik Sri Wahyuni (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2026)
Abstract Health is a condition of physical, mental, spiritual, and social prosperity that allows a person to live a productive life (Law No. 36/2009). Knowledge of drugs is important for the public to avoid the use of counterfeit and illegal drugs, which according to the WHO includes drugs without active ingredients, different ingredients, or with strength that does not match the label. The Community Service Program has been carried out to increase public knowledge, primarily through the role of women, about the dosage form, packaging, safety, and stability of drugs. The activity was carried out using a lecture and discussion method and involved 45 participants from 17 women's organizations in the Magetan area. The results showed that this program succeeded in increasing participants' understanding of drug dosage form, packaging, safety, and stability. This activity also received a positive response from the participants and was reported by local media. The community service program successfully increased the community's knowledge and understanding of drugs and drug stability, thus strengthening SDGs 3. Keywords: Health, medicine, safety, stability, SDGs 3